Zakat distribution in the Federal Territory Islamic Council (MAIWP) of Malaysia: a juristic evaluative study - Hambari, Hambari; Arif, Arif Ali; Artalim Zaim, Muntaha (2022)
This research aims to analyze the experience of the Federal Territory Islamic Council (MAIWP) of Malaysia in the management of zakat and the jurisprudential evaluation of the distribution process. The paper selects MAIWP for analysis as this institution is one of the progressive zakat institutions in Malaysia, located in the capital city, and has applied a modern zakat management system that becomes a reference for other zakat institutions in the country. This research uses three methods including inductive, analytical approaches, and field study to achieve its objectives. This study suggests that the implementation of the distribution of zakat in this organization is strictly for the eight zakat recipients as mentioned in the Quran 9: 60 including the poor, the needy, those working on it, those whose hearts are drawn up, the slaves, the debtors, and for the sake of God, and the stranded traveller. However, the definitions of these groups are according to the concept of contemporary jurisprudence and also based on the country’s circumstances, so some of the eight zakat recipients are given an expansion of description. The research shows that the method of zakat distribution applied in MAIWP has two different types including direct and indirect approaches. It is also found that there are two types of distribution programs, such as consumption-based and distribution-based programs. These are in accordance with Sharia and its objectives.